Differences in the predatory behaviour of male and female ladybird beetles (Coccinellidae) - Jan Šipoš (European Journal of Environmental Sciences, 2012)
We investigated the response of males and females of ladybirds to different densities of aphids. This was studied using Coccinella septempunctata as the predator and Rhopalosiphum padi as the prey. Interactions between this ladybird and prey were observed on barley (Hordeum vulgare). We established aphid colonies on barley at three different densities, 16, 32 and 84 aphids per pot. Adult ladybirds placed in these colonies were then observed for 10 minutes or until they flew away. We hypothesized that females should consume more aphids than males per unit time. The results of this experiment revealed that the risk of aphid mortality per plant depended on the sex of the ladybird beetle. Female ladybirds consumed significantly more aphids than males per unit time. In addition the turning rate and time spent resting differed between the sexes.